Design of the Frozen Soil Roadbed Temperature and Humidity Wireless Monitoring System - MENG Shang-jiu; LI Xiang; SUN Yi-qiang; WANG Miao (Journal of Harbin University of Science and Technology)
The seasonal roadbed of the frozen soil often frost, heave, thaw and settle under the circumstance of frozen and thawed. Among all the factors that cause such damage, temperature and humidity levels are the most significant. According to the problems like too simple measure and monitoring methods, hard to have all space-time monitoring and measure of roadbed and so on in the past, we use remote wireless transmission technique to design two-parameter of monitoring and measure system of temperature and humility in the roadbed of seasonal frozen soil based on the GPRS（General Packet Radio Service） communication technique which can real-timely monitor and measure the change of temperature and humility of the roadbed. The system uses special-purpose soil sensors of temperature and humility as collection terminals; uses STC89C52 single chip as the main controller to achieve remote transmission and storage of data of temperature and humility by editing AT commands to control GPRS network connection and data sending and receiving. We have tested this system and prove that it is a system of high-precision of collection, stabilization, reliability, simple operation which can be used for real-time and undamaged monitoring and measure of temperature and humility of inner-roadbed of seasonal frozen soil.